Mommy and Me - Bortfeld, Heather; Morgan, James L.; Golinkoff, Roberta Michnick; Rathbun, Karen (Psychological Science, 2005)
How do infants find the words in the tangle of speech that confronts them? The present study shows that by as early as 6 months of age, infants can already exploit highly familiar words-including, but not limited to, their own names-to segment and recognize adjoining, previously unfamiliar words from fluent speech. The head-turn preference procedure was used to familiarize babies with short passages in which a novel word was preceded by a familiar or a novel name. At test, babies recognized the word that followed the familiar name, but not the word that followed the novel name. This is the youngest age at which infants have been shown capable of segmenting fluent speech. Young infants have a powerful aid available to them for cracking the speech code. Their emerging familiarity with particular words, such as their own and other people's names, can provide initial anchors in the speech stream.